Effect of intracanal diode laser irradiation on fracture resistance of roots restored with CAD/CAM posts - Flavia Florentino Teixeira da Silva; André Saguchi; Sidnea Aparecida Freitas Paiva; Guilherme Espósito Pires; Mariana Isidoro; Aldo Brugnera Junior; Paulo Francisco Cesar; Ângela Toshie Araki (Brazilian Journal of Oral Sciences, 2021)
Aim: To evaluate the fracture resistance of roots restored with CAD/CAM-fabricated posts, receiving or not intracanal laser treatment, compared with glass fiber posts under mechanical cycling. Methods: Twenty-seven endodontically treated, single-rooted teeth were divided into 3 groups: group 1 (control), prefabricated glass fiber posts relined with resin composite; group 2, CAD/CAM-fabricated intraradicular posts using Resin Nano Ceramic (RNC) blocks; and group 3, CAD/CAM-fabricated intraradicular posts using RNC blocks in canals irradiated with a 940-nm diode laser (100 mJ, 300-um optic fiber, coronal-apical and apical-coronal helical movements, speed of 2 mm/second, 4 times each canal). After cementation of the coping, cyclic loading was applied at an angle of 135° to the long axis of the root, with a pulse load of 130 N, frequency of 2.2 Hz, and 150,000 pulses on the crown at a point located 2 mm below the incisal edge on the lingual aspect of the specimen. Every 50,000 cycles, the specimens were evaluated for root fracture occurring below or above the simulated bone crest. Results were analyzed by one-way ANOVA followed by Tukey’s test (p<0.05). Results: Group 1 was the least resistant, while groups 2 and 3 were the most resistant. Group 1 differed significantly from groups 2 and 3 (p<0.01), but there was no difference between groups 2 and 3 (p<0.01). Conclusion: Treatment of the intracanal surface with diode laser had no influence on fracture resistance of roots restored with CAD/CAM-fabricated posts, but a longer cycling time is required to evaluate the real benefits of diode laser irradiation.